Comparative efficacy of new herbicides in direct seeded rice - Jacob, Geethu; Menon, Meera V; Abraham, C.T. (Journal of Tropical Agriculture, 2014)
A field experiment was conducted during rabi season in a farmer’s field in the Kole lands at Pullu in Thrissur district during the period November 2012 to March 2013. The treatments included application of both pre emergence and post emergence herbicides. The pre emergence herbicides selected were oxyfluorfen sprayed at 3 days after sowing (DAS) and butachlor and pretilachlor sprayed at 6 DAS. Pyrazosulfuron-ethyl, an early post emergence herbicide, was sprayed at 8 DAS. The herbicides cyhalofop butyl, fenoxaprop- p-ethyl, metamifop, penoxsulam, bispyribac sodium and azimsulfuron, are post emergence in action and were sprayed at 20 DAS. Hand weeded (handweeding at 20 and 40 DAS) and unweeded controls were also included for comparison with the herbicide treatments. The best herbicide for control of grass weeds was either fenoxaprop-p-ethyl @ 60 g a.i. ha-1 or cyhalofop butyl @ 80 g a.i. ha-1, both applied at 20 DAS. Broad spectrum weed control can be made possible by spraying herbicide combinations that could give higher yield and B:C ratio.